2020
DOI: 10.1159/000508078
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC2 Alleviates the Progression of Diabetic Nephropathy by Regulating the miR-144/SOCS2 Signalling Axis

Abstract: <b><i>Background:</i></b> Diabetic nephropathy constitutes a large proportion of end-stage kidney failure in diabetic patients. However, the underlying molecular mechanisms remain unclear. <b><i>Methods:</i></b> Db/db diabetic mouse models and high glucose (HG)-induced human renal mesangial cells (HRMCs) were used as research models in vivo and in vitro. The expression of cancer susceptibility candidate 2 (CASC2) was quantified by qRT-PCR. The regulatory role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Li et al found that lncRNA KCNQ1OT1 interference alleviates HG-induced proliferation, oxidative stress and deposition of ECM in HMCs through regulating miR-18b/HMGA2 signaling [ 7 ]. As for lncRNA CASC2, Min et al found that CASC2 attenuates DN development by targeting miR-144/SOCS2 axis [ 9 ]. Zhang et al found that CASC2 is down-regulated in the serum samples of DN patients and HG-treated HMCs, and CASC2 inhibits HG-mediated proliferation, oxidative stress and the accumulation of ECM in HMCs by regulating miR-133b/FOXP1 signaling [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that lncRNA KCNQ1OT1 interference alleviates HG-induced proliferation, oxidative stress and deposition of ECM in HMCs through regulating miR-18b/HMGA2 signaling [ 7 ]. As for lncRNA CASC2, Min et al found that CASC2 attenuates DN development by targeting miR-144/SOCS2 axis [ 9 ]. Zhang et al found that CASC2 is down-regulated in the serum samples of DN patients and HG-treated HMCs, and CASC2 inhibits HG-mediated proliferation, oxidative stress and the accumulation of ECM in HMCs by regulating miR-133b/FOXP1 signaling [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that lncRNA CTBP1-AS2 attenuates HG-mediated oxidative stress, the deposition of ECM, and inflammatory response in mesangial cells by sponging miR-155-5p to induce FOXO1 expression [ 8 ]. lncRNA cancer susceptibility candidate 2 (CASC2) is reported to suppress DN progression through different signaling axes [ 9 , 10 ]. In this study, the working mechanism of CASC2 in DN progression was further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, low expression of CASC2 is identified in a diabetic nephropathy rat model; upregulation of CASC2 can inhibit the inflammatory factor release and further relieve the disease process. 9 Another study also reported the low expression level of CASC2 during the development of ALI, and LPS-induced inflammatory response in the ALI cell model can be suppressed by CASC2 upregulation. 10 These findings supported our results about the potential role of CASC2 in COPD.…”
Section: Discussionmentioning
confidence: 95%
“…Upregulation of CASC2 can inhibit the release of inflammatory factors and further relieve the disease process. 9 Another study has also reported the low expression level of CASC2 during the development of acute lung injury (ALI). Upregulation of CASC2 can alleviate the lipopolysaccharide (LPS)-induced inflammatory response in the ALI cell model.…”
Section: Introductionmentioning
confidence: 99%
“…As Min et al reported, upregulation of CASC2 suppressed inflammatory factor release in high glucose (HG)-induced human renal mesangial cells, thus relieving the progression of diabetic nephropathy. 29 In acute lung injury, CASC2 can inhibit the inflammatory response of cell models. 11 In light of the anti-inflammatory action of CASC2 in asthma cell models, we deduced that CASC2 might be involved in the progression of asthma via regulating Th1/Th2 imbalance and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%